2015
DOI: 10.1111/ced.12657
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of serum levels of osteopontin, selenium and prolactin in patients with psoriasis compared with healthy controls, and their association with psoriasis severity

Abstract: High plasma OPN is a predictor for occurrence of psoriasis. Our study showed that serum selenium and PRL were not decreased in patients with psoriasis, but there was a negative statistically significant correlation between OPN and selenium in all participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 21 publications
3
22
0
Order By: Relevance
“…What is more, OPN concentration did not significantly differ between the group of patients with mild psoriasis and the group with moderate or severe disease severity (p = 0.713). Similar results were obtained by other authors who did not find a relationship between plasma OPN concentration and PASI value 16,21,24,[28][29][30] either. However, different data was presented by Kadry et al, who showed a positive correlation between plasma OPN concentration and the clinical severity of psoriasis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…What is more, OPN concentration did not significantly differ between the group of patients with mild psoriasis and the group with moderate or severe disease severity (p = 0.713). Similar results were obtained by other authors who did not find a relationship between plasma OPN concentration and PASI value 16,21,24,[28][29][30] either. However, different data was presented by Kadry et al, who showed a positive correlation between plasma OPN concentration and the clinical severity of psoriasis.…”
Section: Discussionsupporting
confidence: 91%
“…20 In our study, a significantly higher concentration of OPN in the group of psoriatic patients in comparison to the healthy volunteers (p < 0.001) was observed, which is in agreement with the results reported by other authors. [21][22][23][24] In 2016, Abdel-Mawla et al observed significantly higher OPN expression in the psoriatic plaques in comparison to the healthy skin as well as to the unchanged skin in psoriatic patients. 25 Moreover, the expression of OPN in the unchanged skin of psoriatic patients was significantly higher than in the healthy skin of the healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…OPN is highly expressed in chronic inflammatory and autoimmune diseases. Increased OPN serum levels have been reported in several autoimmune diseases such as rheumatoid arthritis (RA), allergic diseases, Crohn's disease, psoriasis (Robati et al, ; Toossi, Sadat Amini, Sadat Amini, et al, ), and multiple sclerosis (MS) (Lund, Giachelli, & Scatena, ). Recent advances suggest the possibility that OPN could be a promising therapeutic target for autoimmune diseases (Morimoto, Kon, Matsui, & Uede, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies that have compared circulating PRL levels in patients with psoriasis and healthy controls (HCs) and determined the relation between PRL levels and psoriasis severity have shown mixed results . Such disparities may be a result of small sample sizes, low statistical power and/or clinical heterogeneity.…”
Section: Introductionmentioning
confidence: 99%